2006
DOI: 10.1111/j.1574-6976.2006.00017.x
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics in marine larviculture

Abstract: Owing to the problem of antibiotic resistance and subsequent reluctance of using antibiotics, the use of probiotics in larviculture is becoming increasingly popular. During the early stages of development, manipulation of the larval digestive system seems possible through the addition of probiotics either through the culture water or via the livefood. Well-studied probiotics used in human medicine and terrestrial agriculture have proved to be successful in aquaculture and therefore reduce the need for extensiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
227
0
14

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 346 publications
(251 citation statements)
references
References 237 publications
(375 reference statements)
4
227
0
14
Order By: Relevance
“…In aquatic organisms, gut bacterial microbiota is mainly composed of Gram-negative bacteria, being the genera Vibrio, Pseudomonas, and Aeromonas predominant (Vine et al, 2006). Nevertheless, several studies have demonstrated that such bacterial microbiota can be modified by the addition of Gram-positive bacteria in the diet (Ziaei-Nejad et al, 2006;Vieira et al, 2008) or in the culture water (Rengpipat et al 1998;.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In aquatic organisms, gut bacterial microbiota is mainly composed of Gram-negative bacteria, being the genera Vibrio, Pseudomonas, and Aeromonas predominant (Vine et al, 2006). Nevertheless, several studies have demonstrated that such bacterial microbiota can be modified by the addition of Gram-positive bacteria in the diet (Ziaei-Nejad et al, 2006;Vieira et al, 2008) or in the culture water (Rengpipat et al 1998;.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, an alternative that has been widely employed in the aquaculture industry is the dietary supplementation with probiotic bacteria (Gatesoupe, 1999;Vine et al, 2006). Gatesoupe (1999) defines probiotics as "live microbial cells administered to cultured organisms to colonize the digestive tract and improve their immune response".…”
Section: Introductionmentioning
confidence: 99%
“…For example, a probiont may release beneficial digestive enzymes that could enhance digestion and nutrient assimilation, resulting in higher survival of Artemia (Lara-Flores, 2011;Sahu et al, 2008;Wang, 2007). During our study, we fed the Artemia with yeast, thus suggesting our probionts may also provide essential nutrients that by nature do not present in yeast (Vine et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Then, these cultures were used to inoculate Erlenmeyer flasks containing ZoBell's MB, and the flasks were incubated on a rotatory shaker (180 rpm) at 308C. The growth of P.-SW-1 was measured at 600 nm at regular intervals (0, 2,4,6,8,10,12,14,16,18,20,22,24,26,28,30, and 32 h). The absorbance measurement of the sterile ZoBell's MB was used as the blank measurement for each respective well.…”
Section: Growth Characteristics Of P-sw-1mentioning
confidence: 99%
“…Recently, the interest in the use of probiotics in aquaculture has increased. In particular, a variety of in vivo and in vitro studies on the positive effect of using probiotics on fish, shrimp, and molluscs have been performed [12][13][14]. Currently, a number of preparations of probiotics, such as lactic acid bacteria, are commercially available.…”
Section: Introductionmentioning
confidence: 99%